Improved heat and particle flux mitigation in high core confinement, baffled, alternative divertor configurations in the TCV tokamak. (1st December 2022) - Raj, Harshita; Theiler, C.; Thornton, A.; Février, O.; Gorno, S.; Bagnato, F.; Blanchard, P.; Colandrea, C.; de Oliveira, H.; Duval, B.P.; Labit, B.; Perek, A.; et al.
Abstract: Nitrogen seeded detachment has been achieved in the tokamak a configuration variable (TCV) in alternative divertor configurations (ADCs), namely X-divertor and X -point target, with and without baffles in H-mode plasmas with high core confinement. Both ADCs show a remarkable reduction in the inter-ELM particle and heat fluxes to the target compared to the standard divertor configuration. 95%–98% of the inter-ELM peak heat flux to the target is mitigated as a synergetic effect of ADCs, baffling, and nitrogen seeded detachment. The effect of divertor geometry and baffles on core-divertor compatibility is investigated in detail. The power balance in these experiments is also investigated to explore the physics behind the observed reduction in heat fluxes in the ADCs.